Issues and challenges of online learning during covid-19 / Amminudin Ab Latif ...[et al.] - Ab Latif, Amminudin; Mohd Latib, Farah Wahida; Nazarudin, Ainamardia; Bachok, Mohd Fairuz; Othman, Zulhafizal (Universiti Teknologi MARA Cawangan Pahang, 2021)
Coronavirus disease (COVID-19) is now a Global pandemic health problem whereas more than 200 million confirmed cases reported on August 2021with more than 4 million deaths. Malaysia has recorded more than 1 million confirmed cases at mid of August 2021 with a total of 11, 691deaths. The new variants of this virus can infect humans in different ways and the effect varies according to the patient's antibodies or immunity system. The whole world is still in the process of controlling this virus from spreading by means of taking vaccine injections to increase the human immunity system. However, before this vaccine can be given to all, the best way to curb its transmission is by stay at home when there is no essential need to go out. Therefore, in ensuring that the chain of viruses can be terminated, educational institutions such as schools and universities are required to conduct online teaching and learning (T&L) sessions. This transformation of T&L methods brings various issues and challenges to the authorities, educational institutions, educators, students, and even to parents. The objective of this study is to look globally at the issues and challenges faced by those directly involved with online learning and what approaches can be taken to resolve those challenges.